The Critical Height of a Liquid Being Drained from the Tank with Bell-Mouth Drain Port. (8th August 2012) - Mohammadi, J.; Karimi, H.; Islami, M.; Hamedi, M. H.
Abstract : Vortexing occurs during draining of liquid from tanks. We studied the critical height of a liquid being drained from tank, that is, the liquid height at the moment when the air-core vortex reaches to the drain port. We firstly performed some experiments for determining the critical height, and then based upon the information obtained from the experiments; a simple analytical expression was derived to predict the critical height. The experimental results show that the vortex suppressor, which is suggested in the present paper, could effectively reduce the strength of vortex and consequently reduce the critical height. The results also show that the new analytical expression can predict the critical height with less than 20% error when vortex suppressor is used. To the best of our knowledge, draining from tanks with bell-mouth drain ports has not been paid attention to by other authors.